Effect of MELD-Na score on overall survival of periampullary cancer - Yilmaz, Serkan; Yur, Mesut (Springer-Verlag Italia Srl, 2024)
Periampullary cancers have a short overall survival (OS), and many prognostic factors have been studied for this purpose. They usually present with biliary obstruction, which negatively affects the liver, kidney, immune system, and cardiovascular system. This study aimed to investigate the effect of MELD-Na scores on OS in patients undergoing pancreaticoduodenectomy due to periampullary cancer. Patients who underwent pancreaticoduodenectomy due to periampullary cancer between January 2010 and January 2021 were included in the study. After applying the exclusion criteria, 80 of the 124 patients were included in the study. The demographic, laboratory, and pathologic data of the patients were analyzed retrospectively. Univariate analysis showed that MELD-Na score at admission, age-adjusted Charlson Comorbidity Index, adjuvant treatment, portal vein resection, lymphovascular invasion (LVI), T-stage, and tumor location were significantly associated with OS (p < 0.1). In multivariate analysis, MELD-Na score at admission (HR: 1.051, 95% CI [1.004-1.101]; p = 0.033), adjuvant treatment (HR: 4.717, 95% CI [2.371-9.383]; p < 0.001), LVI (HR: 2.473, 95% CI [1.355-4.515]; p = 0.003), and tumor location (HR: 2.380, 95% CI [1.274-4.445]; p = 0.007) were independent risk factors for OS. MELD-Na score, adjuvant treatment, LVI, and tumor location were independent risk factors for the OS of periampullary cancer. The MELD-Na score may be used to predict OS for patients undergoing pancreaticoduodenectomy due to periampullary cancer.
Keywords: MELD-Na score; Pancreatic adenocarcinoma; Pancreaticoduodenectomy